Implementasi Pasal 14 Peraturan Bersama Menteri Agama dan Menteri Dalam Negeri No. 8 dan 9 Tahun 2006 Tentang Pendirian Rumah Ibadah Perspektif Fikih Siyasah : (Studi Kasus Pendirian Gereja di Desa Kampung Perlabian Kec. Kampung Rakyat, Kab. Labuhanbatu Selatan) - Tua Utusan Hasibuan; Iwan, Iwan (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
Joint Regulation of the Minister of Religious Affairs and the Minister of Home Affairs No. 9 and No. 8 of 2006 is a regulation that regulates the provisions of the establishment of houses of worship. In its implementation, this regulation has been debated because the provision to obtain a permit to establish a house of worship depends on the approval of others. This article aims to answer questions about the implementation of article 14 in the joint regulation of the minister of religion and the minister of home affairs No. 8 and 9 of 2006 concerning the establishment of houses of worship (Church) from the perspective of fikih siyasah. In this research using empirical juridical research approach that examines the provisions of the establishment of houses of worship (churches) found in Perlabian Village, Kampung Rakyat Subdistrict, Labuhanbatu Selatan Regency in the Joint Regulation of the Minister of Religion and the Minister of Home Affairs No. 9 and No. 8 of 2006. Furthermore, the regulation is analyzed by using the approach of legislation - invitation, and using library research techniques or literature studies in collecting legal materials. Furthermore, the legal material is processed and analyzed using siy?sah dust?riyyah studies systematically so that it becomes concrete data. The result of this research is the provision of the establishment of houses of worship in Perlabian village, Kampung Rakyat sub-district, has not been fulfilled optimally in its administration such as Building Permit and local community support of at least 60 people authorized by the local village head as contained in article 14 paragraphs 1, 2 and 3 of the Joint Regulation of the Minister of Religion and the Minister of Home Affairs No. 8 and No. 9 of 2006. In line with the above conclusions, the application of the articles in the law should be done by the government that does not cause chaos in the midst of society by enforcing and providing education - education on understanding the applicable law and the government must also be proactive in seeing the situation and conditions in the midst of society in applying the law balanced with local regulations (PERDA) (Labuhan Batu Selatan) to avoid the content of substance that is chaotic in order to have binding legal force.